A Preliminary Study of Optimizing Back Pain Medicinal Cupping Points Disease via Graph Colouring - Nurfatihah, Mohamad Hanafi; Yuhani, Yusof; Mohd Sham, Mohamad; Muhamad Faiz, Abu Bakar; Mohd Adhha, Ibrahim (IOP Publishing, 2019)
Medical cupping is an ancient method that is still used by many people. It is an alternative method in healing process for much type of diseases by using special cups on the specific points of the skin to create suction. Every disease has their specific cupping points. As a habit, practitioners will cup based on patient request or complaint, where it give effect to the cost and time. Thus, the aim of this paper is to study the effective ways on finding the optimum number of cupping points for back pain disease through graph colouring. In addition, a formulation in C# language is given too in validating the graph model result. The finding shows that the optimum number of back pain medicinal cupping points is two.